Prevalence of Orthorexia Nervosa in Spanish university students: relationship with body image and eating disorders - Ruiz Maciá, Alvaro; Quiles Marcos, Yolanda (Anales de Psicología / Annals of Psychology, 2021)
Background. The aim of this study was to examine the prevalence of ON and analyze its relationship with self-image and ED behavior in university students. Method. Cross-sectional study with a sample of 534 Spanish university students, 422 women and 112 men with an age mean of 22,04 (SD= 3,41). Questionnaires administered: a sociodemographic and lifestyle questionnaire, the ORTHO-11-Es, the Teruel Orthorexia Scale (TOS), the Multidimensional Body Self Relations Questionnaire (MBSRQ-45) and the Eating Attitudes Test (EAT-26). Results. 30,5% of the sample were on high risk of developing ON. Higher orthorexic tendencies were observed in women. Those at high risk of ON showed higher BMI, higher proportion of veganism/vegetarianism and significantly higher scores on the MBSRQ-45 (p=,00) and EAT-26 (p=,00). Conclusions. Results showed a high prevalence of ON and its relationship with a worse self-image, concern with physical appearance and ED behaviors.